PROFILE OF PANCASILA RAHMATAN LIL 'ALAMIN STUDENTS FROM AL-QUR'AN HADITH PERSPECTIVE: ANALYSIS OF THOMAS LICKONA'S CHARACTER EDUCATION THEORY - Ishaac, Muhamad; Basir, Abd.; Fuady, M. Noor (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the values in the Profil Pelajar Pancasila Rahmatan Lil ‘Alamin and analyze them from the perspective of the Al-Qur'an hadith and with Thomas Lickona's Knowing, Feeling, and Action character education theory. The method used in this research is literature analysis of Profil Pelajar Pancasila Rahmatan Lil ‘Alamin in government regulations with an interpretive approach to analyze the signs of the Koran and hadith as well as Lickona's theoretical views on Profil Pelajar Pancasila Rahmatan Lil ‘Alamin character education. The results of this research explain that Profil Pelajar Pancasila Rahmatan Lil ‘Alamin character education has 6 dimensions of P5, namely faith, devotion to God Almighty and noble character, global diversity, cooperation, independence, critical reasoning, and creativity, and 10 dimensions of P2RA, namely ta'addub, qudwah, muwatanah, tawassut, tawazun, I'tidal, musawah, shura, tasamuh, tatawwur wa ibtikar which are integrated using 9 principles of holistic, contextual, learner-centered, explorative, togetherness, diversity, independence, usefulness and religiosity which are in line with the values Qur'ani and hadith and prophetic practices by describing the three important components of developing Thomas Lickona's character education to achieve the student profile of Pancasila and rahmatan lil 'alamin by national education goals.